2010
DOI: 10.1093/intqhc/mzq060
|View full text |Cite
|
Sign up to set email alerts
|

Counseling overweight patients: analysis of preventive encounters in primary care

Abstract: Our results indicate that GPs rarely use the check-up program to conduct lifestyle consultations with obese patients. Barriers to lifestyle counseling and possible solutions are discussed with a view to promoting individualized and target management of overweight patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…For example, GPs rarely engage in lifestyle counseling with obese patients during their regular consultations [17]. Further, while many GPs report using verbal counseling for risk factors such as lack of physical activity, they rarely provide referrals or written action plans [18].…”
Section: Importance Of Preventive Care In Optimizing Health Outcomesmentioning
confidence: 99%
“…For example, GPs rarely engage in lifestyle counseling with obese patients during their regular consultations [17]. Further, while many GPs report using verbal counseling for risk factors such as lack of physical activity, they rarely provide referrals or written action plans [18].…”
Section: Importance Of Preventive Care In Optimizing Health Outcomesmentioning
confidence: 99%
“…Patients with a higher BMI receive more physician advice for weight loss and spend more time with the physician than patients who have less severe levels of overweight and obesity. [2,3,12,13] Patients with less education, younger age, and those who have not yet developed weight-related comorbidities are less likely to receive physician counseling. [2] Also, women are more likely than men to receive physician recommendations for weight loss, [7,14] and there is some evidence that physicians recommend greater amounts of weight loss for women than men of comparable weight status.…”
Section: Introductionmentioning
confidence: 99%
“…[18] In one study, female physicians spent more time discussing nutritional information, whereas male physicians were more inclined to discuss cardiovascular risk. [13] However, another study indicated that male patients seeing a male physician received more nutritional and exercise counseling than female patients seeing a female physician. [20] Furthermore, significant differences in the weight loss goals provided by male and female physicians have been documented, with male physicians recommending weight goals to patients that would require significantly greater losses.…”
Section: Introductionmentioning
confidence: 99%
“…This gap between beliefs and practice raises questions regarding the role of primary prevention in GPs’ offices. Thus far, only a few studies have looked at the practice of primary prevention in GPs’ offices [25-28]. The purpose of this study was to understand current primary prevention practices in general care and the attitudes and beliefs that GPs in Germany hold about primary prevention.…”
Section: Introductionmentioning
confidence: 99%